Protocols for Multislice CT - Bruening, Roland; Kuettner, Axel.; Flohr, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
This book provides structured up-to-date information on all routine protocols used for multislice (multidetector row) CT. The volume contains a detailed technical section and covers the prevailing investigations of the brain, neck, lungs and chest, abdomen with parenchymal organs and gastrointestinal tract, the musculoskeletal system and CTA as well as dedicated protocols for the heart. Separate chapters address the how-to of CT-guided interventions such as punctures, drainages, and therapeutic approaches. Each protocol is displayed en bloc, enabling rapid appreciation of indications and the necessary scanner settings. The second edition includes contributions by renowned experts in the field, who not only provide their clinical experience on each topic, but also give guidelines for indications, workflow, postprocessing and reconstruction algorithms.
Technical Principles and Applications of Multislice CT -- Future Perspectives of Multislice CT -- Dose Considerations and Radiation Protection Issues in Multislice CT -- Artifacts in MSCT -- CT of the Heart and Great Vessels: Protocols in Congenital Heart Disease Patients -- Contrast Medium Applications for Multislice CT -- Indication for PET-CT -- Acute Neurovascular Events: Bleeding and Ischemia Diagnosed by MSCT -- CTA of Intracranial Aneurysm -- Imaging of the Cerebral Veins and Sinuses with MS-CT -- Brain Perfusion -- Sinuses and Facial Skeleton -- Nasopharynx, Oropharynx, and Oral Cavity -- MDCT of the Hypopharynx and Larynx -- Multidetector CT-Diagnosis of Infectious Pulmonary Disease -- Parenchymal Changes of the Lung -- MSCT Imaging of Pulmonary Embolism -- Mediastinum, Pleura, and Chest Wall -- Thoracic Aorta -- Calcium Screening -- Coronary Imaging -- Functional Cardiac Imaging -- Bypass Imaging -- Imaging of Coronary Stents -- Coronary Imaging at High Heart Rates -- Diffuse Liver Disease -- Focal Liver Lesions -- MSCT Imaging of Biliary Tract Disease -- MSCT of the Upper Urinary Tract -- Pancreas and Retroperitoneal Space -- Gastrointestinal Tract -- CT Colonography -- Musculoskeletal Imaging -- Trauma Imaging -- CT-Guided Abscess Drainage -- CT-Guided Diagnostic Punctures -- CT-Guided Ablation Therapy -- Vertebroplasty.
Keywords: Medicine; Radiology; Medicine & Public Health; Imaging / Radiology; Electronic books